2021
DOI: 10.3389/fphys.2021.632123
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Incidence and Risk Factors of Myocardial Injury in COVID-19 Patients: A Retrospective Cohort Study

Abstract: Male novel coronavirus disease (COVID-19) patients tend to have poorer clinical outcomes than female patients, while the myocardial injury is strongly associated with COVID-19-related adverse events. Owing to a lack of corresponding data, we aimed to investigate the sex differences in the incidence of myocardial injury in COVID-19 patients and to identify the potential underlying mechanisms, which may partly account for the sex bias in the incidence of adverse events. This retrospective study included 1,157 CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Myocardial injury is another important COVID-19related adverse event and it is sex-dependent. 39 and humoral immunity (HI). 40 RLRs function as intracellular pattern recognition molecules that recognize the virus and facilitate the host immune response.…”
Section: Vadakedath Et Almentioning
confidence: 99%
“…Myocardial injury is another important COVID-19related adverse event and it is sex-dependent. 39 and humoral immunity (HI). 40 RLRs function as intracellular pattern recognition molecules that recognize the virus and facilitate the host immune response.…”
Section: Vadakedath Et Almentioning
confidence: 99%
“…Moreover, WCC, hs‐CRP and d‐dimer were independent risk factors in male patients strongly correlated with hs‐cTnI and BNP changes 99 . It has also been proposed that the inflammatory biomarkers in males were significantly higher than in females in the course of disease progression, highlighting the stronger immune responses in women and robust inflammatory activation in males.…”
Section: The Effects Of Demographic Factors On CV Related Biomarkersmentioning
confidence: 91%
“… 98 Regarding the sex differences, Cheng et al declared that the incidence of myocardial injury among men was higher than women hospitalized due to the COVID‐19 (9.2 vs. 4.9%, p = 0.004). 99 Notably, it can be inferred that affecting ACE2 expression by sex hormones may underlie presumable sex differences in cardiotropic SARS‐CoV‐2 infection. 97 In line with this claim, a recent study reported that androgen signalling has a regulatory effect on ACE2 expression following the SARS‐CoV‐2 infection in human cardiac cells.…”
Section: The Effects Of Demographic Factors On CV Related Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations